2000
DOI: 10.1007/s005350070078
|View full text |Cite
|
Sign up to set email alerts
|

Papillary serous carcinoma of the peritoneum: analysis of clonality of peritoneal tumors

Abstract: Papillary serous carcinoma of the peritoneum (PSCP) is a primary neoplasm of peritoneal origin, and is histologically difficult to differentiate from papillary serous carcinoma of the ovary (PSCO). PSCP is frequently accompanied by many peritoneal tumors, and has been managed as a disseminated disease. In previous reports, however, the clonality of the tumors has not been fully discussed. Recently, the significant roles of the p53 and BRCA1 genes in PSCP have been reported. In this study, we investigated immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…34 In contrast, most studies have suggested that primary peritoneal cancer is multifocal in origin. [35][36][37] Taken together, these potential differences between peritoneal and ovarian cancers imply that future inclusion of peritoneal cancers in studies of epithelial ovarian cancer may be inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…34 In contrast, most studies have suggested that primary peritoneal cancer is multifocal in origin. [35][36][37] Taken together, these potential differences between peritoneal and ovarian cancers imply that future inclusion of peritoneal cancers in studies of epithelial ovarian cancer may be inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…3 Look et al 4 reported the long-term results of cytoreductive surgery for advanced and recurrent epithelial ovarian cancers (18 patients) and papillary serous carcinoma of the peritoneum (10 patients). The median disease-free survival after cytoreduction at their institution was 17.3 months.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Without cytoreductive surgery followed by cisplatin-based chemotherapy, a long-term survival is not normally expected. 3 We experienced an unusual long-term survivor of this tumor and the patient was correctly diagnosed by video-assisted thoracoscopic surgery (VATS) biopsy for the metastatic pleural mass.…”
Section: Introductionmentioning
confidence: 99%
“…Monoclonal models of carcinogenesis are difficult to fit with observations of multifocal, synchronous, or metachronous tumors that characterize neoplasias in some organs. 10,11 Nishimura et al 4 undertook a genetic and immunohistochemical analysis of the expression of the p53 tumor suppressor gene at multiple tumor sites in patients with PSCP to address the question of the clonality of this tumor. 4 Muto et al 12 studied six patients with PSCP and examined eight loci on four chromosomes for loss of heterozygosity.…”
Section: Is Papillary Serous Carcinoma Of the Peritoneum (Pscp) A Mulmentioning
confidence: 99%
“…10,11 Nishimura et al 4 undertook a genetic and immunohistochemical analysis of the expression of the p53 tumor suppressor gene at multiple tumor sites in patients with PSCP to address the question of the clonality of this tumor. 4 Muto et al 12 studied six patients with PSCP and examined eight loci on four chromosomes for loss of heterozygosity. On the basis of these results, they concluded that four of the six patients with PSCP had evidence of many foci.…”
Section: Is Papillary Serous Carcinoma Of the Peritoneum (Pscp) A Mulmentioning
confidence: 99%